THE EFFECT OF EMPLOYEE EMPOWERMENT, WORK RESPONSIBILITY, WORK COMPETENCY, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT VILLAGE AND SUB-DISTRICT OFFICES IN GALANG DISTRICT, BATAM CITY - Umar, Rohisa; Sumardin, Sumardin; Herman, Hendri (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze the influence of employee empowerment, job responsibilities, job competencies, and work motivation on employee performance at the Village and Sub-district Offices of Galang District, Batam City. This research employs a quantitative methodology using a survey approach. The study population comprised all 91 employees of the Village and Sub-district Offices in Galang District, Batam City, employing a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression in SPSS. The results of the study indicate that, in part, employee empowerment, job responsibility, job competence, and work motivation have a significant effect on employee performance. The work motivation variable is the most dominant factor in influencing employee performance. In addition, the results of the simultaneous test prove that all four independent variables together have a significant effect on employee performance. These findings indicate that improving employee performance in government agencies at the village and sub-district levels depends heavily on efforts to empower employees, emphasize job responsibilities, enhance competencies, and manage work motivation in an integrated manner. This study is expected to provide practical contributions to government agency leaders in formulating human resource management policies to improve public service performance.